Sudden sensorineural hearing loss and vertigo associated with arterial occlusive disease: three case reports and literature review - Castro Junior, Ney Penteado de; Almeida, Clemente Isnard Ribeiro de; Campos, Carlos Alberto Herrerias de (São Paulo Medical Journal, 2007)
Sudden sensorineural hearing loss and vertigo (SSNHLV) has multifactorial causes, of which viral, autoimmune and vascular insufficiency are the most common. The therapeutic management for SSNHLV includes antiviral drugs, corticosteroids, vasodilators, normovolemic hemodilution therapy and hyperbaric oxygen therapy. Vertebrobasilar occlusive disease and carotid occlusive disease are seldom related to SSNHLV. Discussions concerning SSNHLV caused by occlusive vascular disease are important and necessary for both neurologists and otolaryngologists, since their therapeutic management and prognosis are very different from other causes of hearing loss and vertigo. Here, we present our experience with three cases managed with interventional treatment and conduct a review and discussion on the relevant literature. We conclude that investigation of vertebrobasilar and carotid occlusive diseases is necessary in patients over 50 years of age who present SSNHLV, mild neurological symptoms and a history of arteriosclerosis, high blood pressure or thrombosis.